Mimicking class I b Mn2-ribonucleotide reductase: A MnII2 complex and its reaction with superoxide - Garcia Melchor, Max; McDonald, Aidan (My University, 2018)
A fascinating discovery in the chemistry of ribonucleotide reductases (RNRs) has been the identification of a dimanganese (Mn2 ) active site in class I b RNRs that requires superoxide anion (O2.- ), rather than dioxygen (O2 ), to access a high-valent Mn2 oxidant. Complex 1 ([Mn2 (O2 CCH3 )(N-Et-HPTB)](ClO4 )2 , N-Et-HPTB=N,N,N',N'-tetrakis(2-(1-ethylbenzimidazolyl))-2-hydroxy-1,3-diaminopropane) was synthesised in high yield (90 %). 1 was reacted with O2.- at -40 °C resulting in the formation of a metastable species (2). 2 displayed electronic absorption features (λmax =460, 610 nm) typical of a Mn-peroxide species and a 29-line EPR signal typical of a MnII MnIII entity. Mn K-edge X-ray absorption near-edge spectroscopy (XANES) suggested a formal oxidation state change of MnII2 in 1 to MnII MnIII for 2. Electrospray ionisation mass spectrometry (ESI-MS) suggested 2 to be a MnII MnIII -peroxide complex. 2 was capable of oxidizing ferrocene and weak O-H bonds upon activation with proton donors. Our findings provide support for the postulated mechanism of O2.- activation at class I b Mn2 RNRs.
PUBLISHED
Keywords: Dioxygen/superoxide activation; Oxidation reactions; Ribonucleotide reductases; Bioinorganic chemistry; Dimanganese complexes